Hypertensive Disorders of Pregnancy: A Literature Review – Pathophysiology, Current Management, Future Perspectives, and Healthcare Disparities - Ariana Traub; Apoorva Sharma; M Carolina Gongora (US Cardiology Review)
Maternal mortality continues to increase in the US, with hypertensive disorders of pregnancy (HDP) remaining one of the leading causes of morbidity and mortality. In this article, the definition, classification, and pathophysiology of the different forms of HDP, current management of these disorders, disparities in prevalence and management of these conditions, and potential strategies to improve HDP outcomes and combat disparities to reduce maternal morbidity and mortality are reviewed. Current management favors a more conservative approach to treating mild chronic hypertension (140–160/90–100 mmHg) in pregnancy. However, recent data suggests active treatment of mild chronic hypertension improves maternofetal pregnancy related outcomes.